2021
DOI: 10.3389/fpls.2020.604938
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Small-Effect Alleles of Indica Origin Enhance High Iron-Associated Stress Tolerance in Rice Under Field Conditions in West Africa

Abstract: Understanding the genetics of field-based tolerance to high iron-associated (HIA) stress in rice can accelerate the development of new varieties with enhanced yield performance in West African lowland ecosystems. To date, few field-based studies have been undertaken to rigorously evaluate rice yield performance under HIA stress conditions. In this study, two NERICA × O. sativa bi-parental rice populations and one O.sativa diversity panel consisting of 296 rice accessions were evaluated for grain yield and leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…Sikirou et al (2018) evaluated more than 2000 O. glaberrima accessions in the Africa Rice Center gene bank at multiple Fe toxic hotspots across West Africa, and identified highly tolerant accessions such as TOG 7250-A, TOG 14367, TOG 7206 and TOG 6218-B. Melandri et al (2021) confirmed the tolerance of some of these accessions. This suggests transferring genes/alleles conferring Fe toxicity tolerance from O. glaberrima to high yielding O. sativa varieties as a promising breeding strategy.…”
Section: Siliconmentioning
confidence: 96%
See 4 more Smart Citations
“…Sikirou et al (2018) evaluated more than 2000 O. glaberrima accessions in the Africa Rice Center gene bank at multiple Fe toxic hotspots across West Africa, and identified highly tolerant accessions such as TOG 7250-A, TOG 14367, TOG 7206 and TOG 6218-B. Melandri et al (2021) confirmed the tolerance of some of these accessions. This suggests transferring genes/alleles conferring Fe toxicity tolerance from O. glaberrima to high yielding O. sativa varieties as a promising breeding strategy.…”
Section: Siliconmentioning
confidence: 96%
“…6 implications for rice breeding 6 .1 Tolerance within the Oryza gene pool Numerous studies have screened sets of varieties or larger germplasm collections in attempts to identify donors for Fe toxicity, typically employing one of two main screening strategies. They may have been conducted in the field in Fe toxic hotspots, evaluating grain yield in addition to biomass and leaf symptoms (Melandri et al, 2021;Pawar et al 2021;Sikirou et al 2018), or they were designed as rapid screens in nutrient solution to which excess Fe had been added at high concentrations for short periods of time (Dufey et al 2015;Matthus et al 2015). From these and other studies it can be concluded that ample genetic variation for tolerance to Fe toxicity exists within theO.…”
Section: Siliconmentioning
confidence: 99%
See 3 more Smart Citations